Consumo energético e eficiência ventilatória dos exercícios respiratórios utilizados em fisioterapia - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Chest physiotherapy includes breathing exercises, widely used in clinical practice, to improve ventilation and lung function, however, there are no studies evaluating energy consumption among breathing exercises. The aim of this study was to evaluate the effects of nine breathing exercises in metabolic, ventilatory and cardiovascular variables in healthy individuals. For that, 17 young healthy individuals were included. Anthropometric and cardiorespiratory measures were performed. After, the breathing exercises Diaphragmatic, Costal Basal, Inspiration in Times, Lapena, Inspiratory Sighs, Breath Shortened, Maximum Inspiration, Maximum Apnea and From the Residual Volume were applied. Prior, each participant was connected to the gas analyzer (VO2000)and measured: oxygen consumption (VO2 ml /kg.min); CO2 production (VCO2 ml / kg.min); minute volume (MV l / min); ratio VE / VO2 and VE /VCO2. All exercises, except Lapena and Maximal Apnea, increased VE values together with increase on VO2 e VCO2. There are not differences in O2consumption and CO2 production in relation to air mobilization, exceptin Lapena, Inspiration in times and Maximal Apnea where a minor energy consumptioncomes with a minor air mobilization. The exercises Diaphragmatic, CostalBasal, Maximum inspiration, Inspiratory Sighs, Breath Shortened and From the Residual Volume, as well as increased energy consumption also improved ventilation, the main objective of breathing exercises. Therefore, these metabolic and cardiorespiratory variables could be used to a better choice and application of these breathing exercises on clinical practice of Physiotherapist.
Energy consumption and ventilatory efficiency of breathing exercises used in physiotherapy
Keywords: Fisioterapia respiratória; Ventilação pulmonar; Consumo de oxigênio; Chest physiotherapy; Pulmonary ventilation; Oxygen consumption; CNPQ::CIENCIAS DA SAUDE